2019
DOI: 10.1093/jue/juz023
|View full text |Cite
|
Sign up to set email alerts
|

Keeping salamanders off the streets: evaluating and modifying one of the first US amphibian road tunnels 30 years after installation

Abstract: Wildlife tunnels are often installed under busy roads to help a variety of animals, from small frogs to bears, safely cross roads that bisect their habitats. One of the first roadway wildlife tunnel systems designed specifically for amphibian use in the USA was installed along Henry Street in Amherst, Massachusetts, in 1987 to protect spotted salamanders (Ambystoma maculatum). These salamanders cross Henry Street during their annual migration to their breeding pools. In recent years, volunteers monitoring the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The activity of toads on paths also suggests that managers should take care to warn any nocturnal visitors to their grounds that they should watch their step. While “Big Night” amphibian migration events do not generally occur in this region, our research and personal observations indicates that paths within protected areas are a major attractant of toads throughout their active period of the year (Hedrick et al, 2019). Our findings also have broader implications in the context of climate change, as the importance of environmental variables indicates the importance of climate and the weather it produces on amphibian behavior.…”
Section: Discussionmentioning
confidence: 58%
“…The activity of toads on paths also suggests that managers should take care to warn any nocturnal visitors to their grounds that they should watch their step. While “Big Night” amphibian migration events do not generally occur in this region, our research and personal observations indicates that paths within protected areas are a major attractant of toads throughout their active period of the year (Hedrick et al, 2019). Our findings also have broader implications in the context of climate change, as the importance of environmental variables indicates the importance of climate and the weather it produces on amphibian behavior.…”
Section: Discussionmentioning
confidence: 58%
“…Hedrick et al. (2019) concluded that modifications to underpasses for salamanders were ineffective, despite an increase in crossings, as they served only a small percentage of the wider population. Thus, limited net loss targets must be underpinned by clear evidence that population persistence is maintained despite reduced levels of movement.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the amount of movement may be considered insufficient, even if it is an improvement over unmitigated conditions. Hedrick et al (2019) concluded that modifications to underpasses for salamanders were ineffective, despite an increase in crossings, as they served only a small percentage of the wider population.…”
Section: What Do We Know About the Effect Of Crossing Structures On W...mentioning
confidence: 99%
“…Overall, permeability of passages to small animal movements appear to vary greatly according to species behavior, location, passage spacing, and passage characteristics (e.g., Lesbarrères et al, 2004;Pagnucco et al, 2012;Beebee, 2013;Langton and Clevenger, 2017;Hedrick et al, 2019;Jarvis et al, 2019;Matos et al, 2019;Schmidt et al, 2020;Boyle et al, 2021). Recent evidence and literature reviews are starting to indicate that wider passages are generally more permeable to more small animal species than small tunnels (e.g., Martinig and Bélanger-Smith, 2016;Langton and Clevenger, 2017;Schmidt et al, 2020), although small tunnels have been shown to be effective for species in some locations, particularly where spacing between passages was short (i.e., Helldin and Petrovan, 2019;Jarvis et al, 2019).…”
Section: Ers and Current Passage Design Considerationsmentioning
confidence: 99%